Raman spectroscopic signals of carotenoid distribution during stages of cell growth of unicellular organisms and plant cells - Badgujar, Pooja Manik; Lin, Yu‐Chung; Lin, Zhe‐Rui; Lin, Ming‐Der; Cheng, Chia‐Liang (Journal of Raman spectroscopy, 2023)
Understanding life at the molecular level is inherently difficult, as no precise method can very specifically determine “The activities of life.” The feasibility to observe the activation of life in an organism using molecular information through Raman spectroscopy in various biological systems is investigated in this work. The idea of determining the “dormant” state to the “growing state” state in complex organisms using specific Raman spectral bands is explained in this study. We found the Raman spectral evidence of carotenoids molecule that shows its appearance from freshwater worms to germinated and non‐germinated seeds. This study investigates the molecular functions of carotenoids in different biosystems. Given the complexity of biological systems, observations from Raman spectroscopic measurements indicate that carotenoids show strong molecular activity when life is growing as compared with a dormant state. We conclude that carotenoid's Raman bands can be considered as the biomarker of growing states in living organisms. In this study, we demonstrate the molecular signature when the life of unicellular organisms and plant cells is in growing or dormant state. We monitored the molecular activity at the dormant and growing state; we conclude carotenoids are present at the dormant stage but migrate and regulate at the growing state. The Raman spectral band of carotenoids can be considered as the “Molecular signature of life activity,” and Raman spectroscopy can be a potential label‐free detection method in understanding the grow/dormant of the life state.